Recruitment of Members of the Independent Election Commission of Aceh for the 2023–2028 Term - Tasha Ramanda; Zainal Abidin; MH, Nurdin (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
The recruitment of members of the Aceh Independent Election Commission (Komisi Independen Pemilihan/KIP) is an important instrument in realizing a democratic, independent, and integrity-based election administration in Aceh, as regulated under Law Number 11 of 2006 concerning the Government of Aceh and Aceh Qanun Number 6 of 2018. However, the implementation of the recruitment process for KIP Aceh members for the 2023–2028 period has raised various issues concerning transparency, objectivity, and the independence of the selection process. This study aims to analyze the recruitment process of KIP Aceh members for the 2023–2028 period, examine the conformity of the nomination process carried out by the Independent Team with statutory provisions, and analyze the legal consequences of KIP Aceh membership recruited in violation of applicable legal requirements. This research employs an empirical legal research method with a prescriptive juridical approach and descriptive empirical analysis. Data were obtained through interviews with relevant stakeholders and library research involving legislation, books, journals, and previous scholarly studies. The findings indicate that the establishment of the Independent Team and the recruitment stages have generally been conducted in accordance with the provisions of the Law on the Government of Aceh and Aceh Qanun Number 6 of 2018. Nevertheless, issues remain regarding the transparency of assessment, objectivity in the selection process, and the potential influence of political interests during the final determination of candidates by the Aceh House of Representatives (DPRA). This study also finds that procedural violations and substantive non-compliance with requirements in the recruitment process may give rise to legal consequences, including administrative lawsuits before the State Administrative Court, annulment of administrative decisions, as well as a decline in public legitimacy and trust in election administrators. Therefore, strengthening transparency, independence, accountability, and supervisory mechanisms is necessary to ensure an objective and professional recruitment process.